Teaching customer service principles using the massive open online course (MOOCs) platform / Noor Azlina Mohamed Yunus ... [et al.] - Mohamed Yunus, Noor Azlina; Ibrahim, Norzawani; Zakaria, Ibhrahim; Zainuddin, Ahmad Zuhairi; Mohd Salleh, Mohammad Zaim; Abd Rahim, Nur Najjah (UiTM Press, 2024)
This study reviewed the effects of a developing MOOC platform for Customer Service Principles course in higher education. Essentially, the Customer Service Principles course is designed to give knowledge and exposure about the fundamental of customer service and discover how to deliver customer service efficiently across various sectors. The development of a MOOC platform is believed to be an interactive learning method to attract and motivate students to clearly understand and to apply this course effectively. The originality of this study is the review of the MOOC platform as an interactive learning method specifically for Customer Service Principles course, something that has been unobserved by previous scholars. This study will contribute to the body of knowledge on the effect of the MOOC platform and to improve the learning activities for higher education institution.